Design of Potential IKK-β Inhibitors using Molecular Docking and Molecular Dynamics Techniques for their Anti-cancer Potential - Singh, Salam P.; Hussain, Iftikar; Konwar, Bolin K.; Deka, Ramesh C.; Singh, Chingakham B. (Current Computer - Aided Drug Design, 2021)
Aim and Objective: To evaluate a set of seventy phytochemicals for their potential ability to bind the inhibitor of nuclear factor kappaB kinase beta (IKK-β) which is a prime target for cancer and inflammatory diseases. Materials and Methods: Seventy phytochemicals were screened against IKK-β enzyme using DFT-based molecular docking technique and the top docking hits were carried forward for molecular dynamics (MD) simulation protocols. The ADME-Toxicity analysis was also carried out for the top docking hits. Results: Sesamin, matairesinol and resveratrol were found to be the top docking hits with a total score of -413 kJ/mol, -398.11 kJ/mol and 266.73 kJ/mol, respectively. Glu100 and Gly102 were found to be the most common interacting residues. The result from MD simulation observed a stable trajectory with a binding free energy of -107.62 kJ/mol for matairesinol, -120.37 kJ/mol for sesamin and -40.56 kJ/mol for resveratrol. The ADME-Toxicity prediction observed that these compounds fall within the permissible area of Boiled-Egg and it does not violate any rule for pharmacological criteria, drug-likeness etc. Conclusion: The study interprets that dietary phytochemicals are potent inhibitors of IKK-β enzyme with favorable binding affinity and less toxic effects. In fact, there is a gradual rise in the use of plant-derived molecules because of its lesser side effects compared to chemotherapy. The study has also provided an insight by which the phytochemicals inhibited the IKK-β enzyme. The investigation would also provide in understanding the inhibitory mode of certain dietary phytochemicals in treating cancer.
Keywords: enzyme